The Features of a current of diseases among the population of the Aral Sea - Ismailova Ozoda (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article there are given information and discussions about current diseases in the areas of Aral Sea and Khorezm region. Some statistics of specific diseases, cause and effects of environmental changes on people’s health in above mentioned areas are included.